Lung function determinants and mortality of children and adolescents with cystic fibrosis in South Africa 2007-2016 - Vandenbroucke, Natalie Joëlle (Department of Paediatrics and Child Health, 2020)
Objectives: Cystic fibrosis (CF) is one of the commonest inherited disorders in South Africa, affecting all population groups. Progressive pulmonary disease with declining forced expiratory volume in one second (FEV1) is the main predictor of morbidity and mortality in individuals with CF. This study aimed to describe the change in lung function, nutritional status and mortality of children and adolescents with CF, attending the Red Cross War Memorial Children’s Hospital (RCWMCH) CF Clinic and to identify factors associated with poor pulmonary function outcomes and mortality. Methods: A retrospective study was conducted of the clinical records and annual pulmonary function tests, with matched body mass index (BMI), of children between 5 and 18 completed years of age attending the RCWMCH CF clinic in Cape Town, South Africa, between January 2007 and December 2016. Results: A total of 143 study participants (51.4% male; median age at diagnosis 5.5 months) were included. Population mean FEV1 and body mass index (BMI) Z scores improved from -2.5  1.70 to -1.9  1.70 (p = 0.1) and from -0.7  1.2 to -0.4  1.2 (p = 0.3) respectively from 2007 to 2016. FEV1 Z score declined by an average of 0.17 per year of age and this was mirrored by an average decline in BMI Z scores of 0.07 for each year of advancing age. FEV1 decline was greater in patients who died compared to those who survived (p = 0.03). Of the factors postulated to influence lung function decline, there was no significant correlation between FEV1 at any age and age of diagnosis, sex, ethnicity, genotype, geographical location, pancreatic status, or Methicillinresistant S. aureus or Aspergillus spp. infection. Participants who were ever infected or colonised with P. Aeruginosa had consistently lower FEV1, however this difference only became significant at certain ages. On multiple stepwise regression analysis, only FEV1 at age 6 was found to be a significant independent predictor of mortality (adjusted odds ratio (95% CI) 0.5 (0.3 – 0.8); p = 0.005). Conclusion: Pulmonary function of children with cystic fibrosis improved non-significantly over the 10-year study period. FEV1 at age 6 was identified as an independent predictor for CF-related mortality. Early diagnosis and measurement of pulmonary function in young children with CF is essential to identify children at risk of poor outcomes.